MIMO radar DOA element position error correction method based on overlapping reference element matrix reconstruction - Tian, Feng; Wei, Tianyu; Fu, Weibo; Wang, Siyuan (Scientific reports, 2025)
Aiming at the problem of the degradation of angle estimation performance of the MUSIC algorithm due to the position error of the array element, this paper proposes a MIMO radar DOA array element position error correction method based on overlapping reference array element matrix reconstruction. This method uses overlapping virtual array elements as references, corrects the array element position error by phase difference, and constructs an error compensation matrix to eliminate the virtual array position error. At the same time, the nuclear norm optimization is introduced to reconstruct the Toeplitz structure to reduce the influence of system noise and array element disturbance on angle estimation, and the MUSIC algorithm is used to achieve accurate angle estimation. Simulation results show that the angle estimation error of this method is 0.2 under a signal-to-noise ratio of 20 dB. The actual traffic scene verification shows that this method effectively improves the angle resolution capability of the MUSIC algorithm and meets the requirements of radar accuracy for traffic applications.